2001
DOI: 10.1161/01.cir.103.10.1382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Testosterone on Plaque Development and Androgen Receptor Expression in the Arterial Vessel Wall

Abstract: Background-Recent studies have suggested that testosterone has a protective effect in the arterial vascular system. However, little is known about the molecular aspects of the mechanism(s) involved in these processes. The aim of the present study was to investigate the effect of testosterone on neointimal plaque development and on the expression of the vascular androgen receptor. Methods and Results-Neointimal plaque formation was induced by endothelial denudation in the aortas of male New Zealand White rabbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 23 publications
3
79
1
4
Order By: Relevance
“…In follow-up studies, those patients with a low testosterone blood level had bigger changes in CIMT over time, representing increased atheroma progression (19,20). Prospective animal studies are consistent with this and have shown that physiological androgen replacement inhibits atheroma progression (11,(21)(22)(23). There are currently no in vivo human data on the effects of androgen therapy on atheroma.…”
Section: Introductionmentioning
confidence: 76%
“…In follow-up studies, those patients with a low testosterone blood level had bigger changes in CIMT over time, representing increased atheroma progression (19,20). Prospective animal studies are consistent with this and have shown that physiological androgen replacement inhibits atheroma progression (11,(21)(22)(23). There are currently no in vivo human data on the effects of androgen therapy on atheroma.…”
Section: Introductionmentioning
confidence: 76%
“…Many, but not all, of the previous studies indicated that testosterone might inhibit VSMC growth. Hanke et al 113 reported, using an ex vivo organ culture system, that testosterone at 10-100 ng ml -1 significantly inhibited neointima formation in association with increased expression of AR in endothelium-denuded rabbit aortic rings after 21 days of incubation. Somjen et al 114 demonstrated the dose-dependent inhibitory effects of dihydrotestosterone and membrane-impermeable testosterone on DNA synthesis in cultured VSMCs derived from the human umbilical artery, suggesting a role for membrane AR.…”
Section: Effects Of Testosterone On Ecsmentioning
confidence: 99%
“…Low testosterone level is also associated with poor vasodilation of the brachial artery and is an independent risk factor for endothelial dysfunction in men (Akishita et al 2007). Androgen replacement has been shown to prevent aortic atherosclerotic changes in castrated male rabbits fed a high cholesterol diet (Alexandersen et al 1999), and arterial AR mRNA upregulation by testosterone has been shown to reduce neointimal plaque formation in male rabbits (Hanke et al 2001). Endogenous testosterone also inhibits coronary neointimal formation after balloon injury through enhanced expression of PKC d and p27 (kip1; Tharp et al 2009).…”
Section: Effects Of Androgens On Vascular Remodelingmentioning
confidence: 99%